VD_FINDINFO Arrêt / 2014 / 187 vom 27. März 2014 - VD Tribunal cantonal (2014)
AM, RÉDUCTION DES PRIMESAM, MÉNAGE COMMUN | 65 LAMal, 11 LVLAMal, 12 LVLAMal, 9 LVLAMal, 23 RLVLAMal, 10 al. 1 let. d LHPS, 9 LHPS, 12 RLHPS